2009
DOI: 10.1111/j.1346-8138.2009.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative pigmented squamous cell carcinoma in a 101‐year‐old Japanese woman

Abstract: Pigmented squamous cell carcinoma is a rare variant of squamous cell carcinoma. We report a case of pigmented squamous cell carcinoma with dermoscopic examination probably arisen from actinic keratosis in a 101-year-old woman who was surgically treated under general anesthesia. In addition, we discuss indications of general anesthesia in elderly patients with skin cancer, differential diagnosis and dermoscopic features of pigmented squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…On the basis of our and previous reports, PCSCC should be considered when dealing with a pigmented lesion characterized by an unspecific dermoscopic pattern with the features of diffuse blue-gray pigmentation, scaling, polymorphic vessels and radial structures [1,6,8,9]. …”
Section: Answer and Explanationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of our and previous reports, PCSCC should be considered when dealing with a pigmented lesion characterized by an unspecific dermoscopic pattern with the features of diffuse blue-gray pigmentation, scaling, polymorphic vessels and radial structures [1,6,8,9]. …”
Section: Answer and Explanationmentioning
confidence: 99%
“…PCSCC is a variant of invasive squamous cell carcinoma, with less than 20 cases reported, to our knowledge, in the English literature [1,2]. PCSCC had been more often reported to occur in the oral mucosa and conjunctiva [3].…”
Section: Answer and Explanationmentioning
confidence: 99%
“…A small number of cases (less than 40) of SCC which contain a population of non neoplastic melanocytes, called pigmented SCCs have been reported In the English literature [5,6]. Most of these neoplasms have been described on mucosal surfaces such as the oral and nasal cavity, the conjunctiva [7][8][9][10][11][12][13][14][15][16][17][18] and the uterine cervix [19], as well as on sun-exposed skin such as the head and neck region where 19 cases of pigmented SCC have been described until 2011 [6,[20][21][22][23][24][25][26][27][28][29]. In addition, a case of subungual pigmented SCC has recently been reported [30].…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the studies have found face as the most common site. In 2009, Yoshida et al reported a 2.2x1.5 cm pigmented SCC on the nose of a 101-year-old Japanese woman [6]. In most of the previously reported cases, common age at presentation was old age [7,8].…”
mentioning
confidence: 99%